Modeled variations in the inherent optical properties of summer Arctic ice and their effects on the radiation budget: a case based on ice cores from 2008 to 2016 - Yu, Miao; Lu, Peng; Leppäranta, Matti; Cheng, Bin; Lei, Ruibo; Li, Bingrui; Wang, Qingkai; Li, Zhijun (Copernicus Publications, 2024)
Variations in Arctic sea ice are apparent not only in its extent and thickness but also in its internal properties under global warming. The microstructure of summer Arctic sea ice changes due to varying external forces, ice age, and extended melting seasons, which affect its optical properties. Sea ice cores sampled in the Pacific sector of the Arctic obtained by the Chinese National Arctic Research Expedition (CHINARE) during the summers of 2008 to 2016 were used to estimate the variations in the microstructures and inherent optical properties (IOPs) of ice and determine the radiation budget of sea ice based on a radiative transfer model. The variations in the volume fraction of gas bubbles (Va) of the ice top layer were not significant, and the Va of the ice interior layer was significant. Compared with 2008, the mean Va of interior ice in 2016 decreased by 9.1 %. Meanwhile, the volume fraction of brine pockets increased clearly during 2008–2016. The changing microstructure resulted in the scattering coefficient of the interior ice decreasing by 38.4 % from 2008 to 2016, while no clear variations can be seen in the scattering coefficient of the ice top layer. These estimated ice IOPs fell within the range of other observations. Furthermore, we found that variations in interior ice were significantly related to the interannual changes in ice ages. At the Arctic basin scale, the changing IOPs of interior ice greatly changed the amount of solar radiation transmitted to the upper ocean even when a constant ice thickness is assumed, especially for thin ice in marginal zones, implying the presence of different sea ice bottom melt processes. These findings revealed the important role of the changing microstructure and IOPs of ice in affecting the radiation transfer of Arctic sea ice.